2022
DOI: 10.1038/s41598-022-12351-w
|View full text |Cite
|
Sign up to set email alerts
|

Reduced body length and morphological disorders in Chrysomya albiceps (Diptera: Calliphoridae) larvae reared on aluminum phosphide-treated rabbits

Abstract: Assessing the time of death based on the growth and development of insects is a critical task in forensic entomology. The rate of larvae development can be affected by a variety of toxins, including pesticides. Aluminum phosphide (AlP) is a low-cost insecticide that has yet to be tested for entomotoxicological significance, despite the fact that it is frequently the cause of fatal poisoning. In this study, we measured the body length of Chrysomya albiceps larvae reared on the carcasses of rabbits poisoned with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…The average length, width and weight of larvae that fed in the treated group were significantly lower compared to the control. The present results are supported by the study of El-Ashram et al (2022) who reported that C. albiceps flies that reared on AlP administered rabbits’ carcasses had a significantly lower gain in body length compared to control carcasses. Other toxins have different effects on the size of insects; ketamine was reported to have no significant effect on the larvae's length and weight ( Zou et al, 2013 ).…”
Section: Discussionsupporting
confidence: 88%
“…The average length, width and weight of larvae that fed in the treated group were significantly lower compared to the control. The present results are supported by the study of El-Ashram et al (2022) who reported that C. albiceps flies that reared on AlP administered rabbits’ carcasses had a significantly lower gain in body length compared to control carcasses. Other toxins have different effects on the size of insects; ketamine was reported to have no significant effect on the larvae's length and weight ( Zou et al, 2013 ).…”
Section: Discussionsupporting
confidence: 88%
“…This successful application of Hg analysis in entomological specimens guided the police investigation accurately. In a recent study, El-Ashram et al (2022) Extracted aluminum phosphide (AlP) (is a low-cost insecticide, rodenticide and fumigant) from a pooled sample of the 3 rd instar larvae of Ch. albiceps.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar vein, studies by Nolte et al (1992) and Kintz et al (1994) reported that drug concentrations in maggots were significantly lower than those in tissues. In addition, El-Ashram et al (2022), found the concentration of aluminum phosphide in the 3rd larvae body was significantly lower than in rabbit tissues.…”
Section: Discussionmentioning
confidence: 96%
“…This result agreed with Afifi et al (2022), who recorded the presence of clonazepam inside all larval instars of Sarcophaga argyrostoma. Also, El-Ashram et al (2022) stated the existence of aluminum phosphide in third-instar larvae of Chrysomya albiceps.…”
Section: Discussionmentioning
confidence: 99%